(untitled) (Human Factors in Design, 2024)
The experiences lived during pregnancy can influence the quality of motherhood. When it comes to pregnant women with disabilities, the challenges are even greater. This study aimed to identify, through a systematic search, studies on the practices of aid and support for the preparation of disabled pregnant women and health professionals related to childbirth, in order to establish a picture of the current situation of how these women are being supported in Brazil and in the world. As a result, it was found that most studies report the experiences of both disabled pregnant women and health professionals, the needs of both in relation to their interactions, and few are discussed about solutions for these needs, demonstrating the relevance of this discussion.